2008
DOI: 10.1111/j.1600-0757.2008.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical emergencies in the dental practice

Abstract: Medical emergencies occurring in dental practice can be alarming. The keys to minimizing alarm are taking a thorough history so that possible emergencies can be, to some extent, anticipated, and having a good working knowledge of how to manage emergencies, should they arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…This clearly indicates that dentists should expect to be crucially involved in the diagnosis and management of medical emergencies. (5,10) The most common of these emergencies was syncope, followed by hypoglycaemia, hypertensive crisis, anaphylaxis and seizures; however, in most cases the emergencies were not life-threatening. Our reported relative incidence of medical emergencies is gen- erally congruent with previous studies (3,5,9) and reemphasizes the urgency of a new professional consciousness of dentists regarding their expectation of and preparedness to effectively manage medical emergencies in their office.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clearly indicates that dentists should expect to be crucially involved in the diagnosis and management of medical emergencies. (5,10) The most common of these emergencies was syncope, followed by hypoglycaemia, hypertensive crisis, anaphylaxis and seizures; however, in most cases the emergencies were not life-threatening. Our reported relative incidence of medical emergencies is gen- erally congruent with previous studies (3,5,9) and reemphasizes the urgency of a new professional consciousness of dentists regarding their expectation of and preparedness to effectively manage medical emergencies in their office.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a thorough medical history can help to reduce the risk of medical emergencies. (10) We showed that among Slovenian dentists, a general medical history is taken and written down in the medical Figure 1. Estimation of competence for dentists who had never participated in BLS (basic life support) training before (■) (n= 38) and dentists who had already participated in BLS training at least once (•) (n=217).…”
Section: Discussionmentioning
confidence: 99%
“…In the 8 works on the management of those situations, 4 encourage or suggest the use of IV access [16,18,21,22]. Thus, IV injection remains one of the main techniques proposed for the management of medical emergencies within dental literature.…”
Section: Publications On Medical Emergencies In Dental Practicementioning
confidence: 99%
“…In the 7 works about equipment recommended to face medical emergencies, 4 suggest to have some intravenous drugs [13,[16][17][18]. In the 8 works on the management of those situations, 4 encourage or suggest the use of IV access [16,18,21,22].…”
Section: Publications On Medical Emergencies In Dental Practicementioning
confidence: 99%
See 1 more Smart Citation